Cutaneous features of Zika virus infection: a clinicopathological overview. (1st January 2019) - Paniz‐Mondolfi, A. E.; Blohm, G. M.; Hernandez‐Perez, M.; Larrazabal, A.; Moya, D.; Marquez, M.; Talamo, A.; Carrillo, A.; Rothe de Arocha, J.; Lednicky, J.; Morris, J. G.
Summary: Zika virus (ZIKV) is an emerging mosquito‐borne flavivirus transmitted mainly by Aedes species of mosquitos. Although the infection is usually mild and self‐limiting, it is emerging as a public health challenge in tropical and subtropical countries owing to its unprecedented pathogenicity and increased risk for fetal malformations and neurological symptoms. Cutaneous manifestations as for other mosquito‐borne viruses remain a hallmark of the disease. This article provides a detailed overview on ZIKV infection, including its varied cutaneous clinical manifestations and diagnostic aspects, and also provides detailed insights into its pathogenesis in human skin. Abstract : Click here for the corresponding questions to this CME article.